THE DIVISION OF INHERITANCE OF CHINESE CUSTOMS IN THE SOUTHERN CITY OF GORONTALO - Bempa, Sofyan W.P; Kasim, Nur Mohamad; Jasin, Johan (Journal of Humanity, 2017)
The purpose of this research is (1) to know the implementation of the Division of property of the heritage of indigenous people in the Chinese community in the city of Gorontalo, (2) to find out how to dispute the inheritance in Chinese society in the indigenous town of Gorontalo. This type of research is empirical legal research, legal research is the socio-type research, engineering analysis with qualitative data sourced from primary data and secondary data. In addition to using normative approaches, sociology and historical approach.Based on the results of the research, it can be concluded that (1) the implementation of the Division of indigenous heritage in Chinese society in the city of Gorontalo is based on an agreement with the family (the heir). Whereas in the Straits Chinese community assimilated local customs in this custom of Gorontalo, embraced the parental kinship system, in which seat boys and girls equally so in the Division of the inheritance rights of boys and girls equal rights, (2) on the Chinese community in the city of Gorontalo, rarely there is a dispute of inheritance. If there is a dispute, then how are customary inheritance dispute resolution on the Chinese community in the city of Gorontalo is by way of a limited discussion in the sphere of the family, and trying not to let the issue be brought to the level of the Court, because Chinese society is considered a disgrace if family until there is a dispute between the fellows family just because a matter of inheritance